2021
DOI: 10.1007/s11159-021-09902-0
|View full text |Cite
|
Sign up to set email alerts
|

Educational disruptions during the COVID-19 crisis in Small Island Developing States: Preparedness and efficacy of academics for online teaching

Abstract: COVID-19 has caused a global rush of universities to transfer their courses online to maintain continuity in student teaching and learning. The study presented in this article investigated the preparedness of academics in Small Island Developing State (SIDS) universities for shifting to emergency online teaching. To examine the impact of preparedness and other factors on the efficacy of academic staff in performing their work duties during the pandemic, the research team collected data from 75 respondents who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In that perspective, this study also, on the other hand, note that most HEIs are not readily prepared to face those challenges of adopting the new digital technologies and its underlying global reality and/or transformational benefits (Boninger et al, 2019(Boninger et al, , 2020CONECTA, 2021a;Cuban, 2020OECD, 2015OECD, , 2021. The lack of preparedness became patent when the universities and faculties were forced to shift to a completely-digital modality due to the recent Covid-19 pandemic (Aguilera-Hermida et al, 2021;Almaiah et al, 2020;Al-Maskari et al, 2021;Aristovnik et al, 2020;Armstrong-Mensah et al, 2020;Blackman et al, 2020;Burgess & Sievertsen, 2020;Crawford et al, 2020;Crick et al, 2020;Devkota, 2021;di Pietro et al, 2020;Ma et al, 2021;Mncube et al, 2021;OECD, 2020bOECD, , 2021Oyedotun, 2020;Peres et al, 2020;Pokhrel & Chhetri, 2021;Reimers et al, 2020;Rogers & Shwetlena, 2020;Sánchez-Cruz et al, 2021;Seetal et al, 2021;UN, 2021;UNESCO, 2020;Viner et al, 2020). Besides, a larger part or reason for such lack of readiness may be attributed to the unavailability of infrastructures, digital literacy skills, or limited resources in the region (LALA, 2020;Sánchez-Cruz et al, 2021;UNESCO, 2021a, b).…”
Section: Discussionmentioning
confidence: 99%
“…In that perspective, this study also, on the other hand, note that most HEIs are not readily prepared to face those challenges of adopting the new digital technologies and its underlying global reality and/or transformational benefits (Boninger et al, 2019(Boninger et al, , 2020CONECTA, 2021a;Cuban, 2020OECD, 2015OECD, , 2021. The lack of preparedness became patent when the universities and faculties were forced to shift to a completely-digital modality due to the recent Covid-19 pandemic (Aguilera-Hermida et al, 2021;Almaiah et al, 2020;Al-Maskari et al, 2021;Aristovnik et al, 2020;Armstrong-Mensah et al, 2020;Blackman et al, 2020;Burgess & Sievertsen, 2020;Crawford et al, 2020;Crick et al, 2020;Devkota, 2021;di Pietro et al, 2020;Ma et al, 2021;Mncube et al, 2021;OECD, 2020bOECD, , 2021Oyedotun, 2020;Peres et al, 2020;Pokhrel & Chhetri, 2021;Reimers et al, 2020;Rogers & Shwetlena, 2020;Sánchez-Cruz et al, 2021;Seetal et al, 2021;UN, 2021;UNESCO, 2020;Viner et al, 2020). Besides, a larger part or reason for such lack of readiness may be attributed to the unavailability of infrastructures, digital literacy skills, or limited resources in the region (LALA, 2020;Sánchez-Cruz et al, 2021;UNESCO, 2021a, b).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dhruba Kumar Gautam and Prakash Kumar Gautam analysed the perception of faculty members and higher education students about the online mode of teaching adopted by Nepal during the COVID-19 pandemic; they found that the effectiveness of online classes depended on three main factors: infrastructure, students and teachers (Gautam and Gautam 2021 ). Isma Seetal et al ( 2021 ) found that in Small Island Developing States (SIDS), a designation referring to a group of developing countries with a number of distinctive vulnerabilities, learning loss occurred because teachers “lacked adequate training” in using technologies (Seetal et al 2021 , p. 185).…”
Section: The Impact Of the Pandemic: A Literature Reviewmentioning
confidence: 99%
“…LDCs’ education sector is affected as much as their health sector. Teaching–learning activities in sub-Saharan Africa and South Asia (the regions where the majority of LDCs are located), came to a standstill during the pandemic because of a lack of electricity, computers and internet infrastructure (Seetal et al 2021 ). Educational institutions were unable to move to online instruction because only about 18% of the population in LDCs have access to the internet (Bhattacharya and Islam 2020 ).…”
Section: Analysis and Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of educational technology and computer-assisted learning has brought many changes to higher education ( Seetal et al, 2021 ). Over the past three decades, online learning has become an important part of the higher education system.…”
Section: Introductionmentioning
confidence: 99%